2013
DOI: 10.1212/wnl.0b013e318288690c
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Alzheimer disease in subjects with amnestic and nonamnestic MCI

Abstract: AD biomarkers are useful to predict AD-type dementia in subjects with aMCI and naMCI. However, biomarkers might not be as sensitive for early diagnosis of AD in naMCI compared with aMCI. This may have implications for clinical implementation of the National Institute on Aging and Alzheimer's Association criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(90 citation statements)
references
References 30 publications
5
81
0
4
Order By: Relevance
“…On the other hand, to analyze in depth the 14 11 C-PIB-positive MCI patients, the amnestic and nonamnestic nature deserves to be considered. [30][31][32][33] Remarkably, of the 10 NA-MCI patients, PIB was negative in all of them. Therefore, amyloid deposit was excluded, and AD would be very unlikely; in others words, this would mean that all NA-MCI patients are very unlikely to be PIB positive, and hence to have β-amyloid protein deposits (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, to analyze in depth the 14 11 C-PIB-positive MCI patients, the amnestic and nonamnestic nature deserves to be considered. [30][31][32][33] Remarkably, of the 10 NA-MCI patients, PIB was negative in all of them. Therefore, amyloid deposit was excluded, and AD would be very unlikely; in others words, this would mean that all NA-MCI patients are very unlikely to be PIB positive, and hence to have β-amyloid protein deposits (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…3,17,19,27,[29][30][31][32]43 Two studies included in this meta-analysis assessed hippocampus volume by MRI and amyloid burden by PET in the same patients. 29,32 These studies reported higher odds ratios/positive predictive value/negative predictive value/accuracy for amyloid PET than MRI hippocampus volume reduction on MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Two papers did not indicate the criteria used to diagnosis AD 13,16 and one paper used IWG criteria. 44 Some studies satisfied both NINCDS-ADRDA and DSM-IV criteria, 22,23,[26][27][28]31,38 and others used only one set of criteria. Some studies that used NINCDS-ADRDA criteria adopted probable AD, 10,12,14,17,[19][20][21]23,[26][27][28][29]32,33 whereas other studies did not indicate the diagnosis as probable or possible AD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although many are proven effective at the sites where they are developed, dissemination of these advanced analytical techniques between institutions has proven challenging (32)(33)(34)(35). Like CSF measurements, sensitivity and specificity of hippocampal volume calculations have shown limited ability to predict who will convert from MCI to AD and are often combined with other biomarkers (36)(37)(38)(39)(40).…”
Section: Current Status Of Tests For Admentioning
confidence: 99%